2020
DOI: 10.1136/annrheumdis-2020-218881
|View full text |Cite
|
Sign up to set email alerts
|

Anti-centromere antibodies target centromere–kinetochore macrocomplex: a comprehensive autoantigen profiling

Abstract: ObjectivesAnti-centromere antibodies (ACAs) are detected in patients with various autoimmune diseases such as Sjögren’s syndrome (SS), systemic sclerosis (SSc) and primary biliary cholangitis (PBC). However, the targeted antigens of ACAs are not fully elucidated despite the accumulating understanding of the molecular structure of the centromere. The aim of this study was to comprehensively reveal the autoantigenicity of centromere proteins.MethodsA centromere antigen library including 16 principal subcomplexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Several studies of epitope specificity have demonstrated that anti-CBX5 and anti-CENP-C are more common in SS than SSc patients [ 5 ]. However, a recent study of autoantigen profiling of ACA showed similar reactivities against centromere antigens in SS and SSc, unlike previous reports, and ACA-positive SS, SSc, and PBC patients had common clinical characteristics [ 13 ]. A further study should investigate if Korean SS patients with ACA have distinct epitopes from SSc and PBC patients with ACA.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Several studies of epitope specificity have demonstrated that anti-CBX5 and anti-CENP-C are more common in SS than SSc patients [ 5 ]. However, a recent study of autoantigen profiling of ACA showed similar reactivities against centromere antigens in SS and SSc, unlike previous reports, and ACA-positive SS, SSc, and PBC patients had common clinical characteristics [ 13 ]. A further study should investigate if Korean SS patients with ACA have distinct epitopes from SSc and PBC patients with ACA.…”
mentioning
confidence: 92%
“…A retrospective Japanese study reported that 81 (37.9%) of 309 ACA-positive patients were ultimately diagnosed with SSc, and 50 (23.4%) with SS [ 12 ]. Furthermore, it was recently reported that ACA-secreting cells accumulate in the salivary glands of SS patients [ 13 ]. Therefore, researchers have been examining the clinical characteristics of ACA-positive SS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Figure 3 As a popular antinuclear antibody to detect autoimmune diseases, the expression of anti-CENP-B in SS patients also has certain characteristics. In this group, we included 9 studies with corresponding data, recorded the number of SS patients with positive expression of anti-CENP-B, the total number of patients studied, the number of patients with positive expression of anti-SSB in the control group, and the total number of patients in the control group, and input the data into Revman for forest map analysis [13]. As shown in Figure 3-4, the results of four studies intersect with the invalid line, three of which are in favor of the side against SSB, and only one study is slightly in favor of the side of anti-CENP-B.…”
Section: The Results Of Funnel Plot Analysismentioning
confidence: 99%
“…It was suggested that neonates after exposure to anti-RO/La autoantibodies demonstrate innate immune activation, which was mainly related to IFN-γ producted by NK cells, CD4 + T cells and CD8 + T cells [48]. Additional study indicated that anti-centromere antibodies (ACAs) in the cytoplasm were detected in pSS and were associated with the accumulation of SGs centromere antibody secreting cells (ASCs) [49]. However, one study proposed that GO analysis was signi cantly different in salivary and lacrimal glands in time series [45].…”
Section: Discussionmentioning
confidence: 99%